Modeling of carbon dioxide adsorption onto ammonia-modified activated carbon: Kinetic analysis and breakthrough behavior - Shafeeyan, M.S.; Daud, W.M.A.W.; Shamiri, A.; Aghamohammadi, N. (American Chemical Society, 2015)
The removal of carbon dioxide from the flue gas of fossil-fueled power plants can be achieved using adsorption separation technologies. In this study, the breakthrough adsorption of CO2 on fixed beds of commercial granular activated carbon (GAC) and ammonia-modified GAC (OXA-GAC) adsorbents was measured. The breakthrough curves were acquired from dynamic column measurements at temperatures ranging from 30 to 60 °C with a feed gas flow rate that varied from 50 to 100 mL min–1 and a total pressure of 1.0 atm. An earlier breakthrough time and lower dynamic adsorption capacity were observed with increasing temperature, increasing feed flow rate, and the use of the GAC adsorbent. The largest CO2 equilibrium dynamic capacity (0.67 mol kg–1) and breakthrough time (10.9 min) over the range of operating conditions investigated were obtained using OXA-GAC adsorbent at 30 °C under a 50 mL min–1 feed flow rate. To predict the breakthrough behavior of the fixed-bed adsorption of CO2, a simple model based on mass balance was developed. This model consists of an Avrami equation to describe the kinetics of adsorption and a semiempirical Toth equation to represent the gas–solid equilibrium isotherm. The Avrami equation was selected because it provided the best fit with the experimental kinetic curves for both adsorbents, with average relative errors of less than 2% over the temperature range of 30–60 °C. The resultant set of coupled differential equations was solved using a numerical approach based on the finite element method implemented in COMSOL Multiphysics software. The findings showed that the model predictions successfully fit the experimental data over the studied range of feed gas flow rates and adsorption temperatures.